"Write Me a Better Story": Writing Stories as a Diagnostic and Repair Practice for Automotive Technicians. (April 2015) - Cushman, Jeremy
Although storytelling research is rarely applied to technical communication, I approach it as one way of technical communication practitioners and teachers might account for the social, creative, knowledge-intensive ways technical service work gets done. In particular, I look to the technical service work of automotive technicians at a repair shop in the Northwest. These technicians not only tell each other stories, but they also write stories about their diagnostic practices, or what they do to determine problems, and about their processes for addressing those problems—their actual repair work. But writing stories is more than instrumental. I argue that acts of storytelling are inseparably entangled with acts of accessing technical breakdowns, determining possible problems, and then producing acceptable solutions. For these technicians, writing stories and fixing cars intertwine. My central question, then, is how can technical communication researchers and teachers approach acts of storytelling in ways that offer us richer, more precise articulations of the relationship between writing and technical service work like that of fixing cars?